Cloning, sequencing, and expression of the gene encoding methylmalonyl-coenzyme A mutase from Streptomyces cinnamonensis. - Birch, A (1993)
In streptomycetes, the conversion of succinyl-coenzyme A (CoA) into methylmalonyl-CoA, catalyzed by methylmalonyl-CoA mutase, most likely represents an important source of building blocks for polyketide antibiotic biosynthesis. In this work, the structural gene for methylmalonyl-CoA mutase from Streptomyces cinnamonensis was cloned by using a heterologous gene probe encoding the mutase from Propionibacterium shermanii. A 5,732-bp fragment was sequenced, within which four open reading frames were identified on one DNA strand. The two largest (mutA and mutB) overlap by 1 nucleotide and encode proteins of 616 and 733 residues showing high amino acid sequence similarities to each other and to methylmalonyl-CoA mutases from P. shermanii and mammalian sources. The transcriptional start of the mutA-mutB message, determined by S1 mapping, coincides with the first nucleotide of the translational start codon. Evidence that these two open reading frames encode a functional mutase in S. cinnamonensis was obtained by subcloning and expression in Streptomyces lividans TK64. The mutA and mutB gene products were detected in Western blots (immunoblots) with mutase-specific antibodies and by direct detection of mutase activity with a newly developed assay method. The methylmalonyl-CoA mutase was unable to catalyze the conversion of isobutyryl-CoA into n-butyryl-CoA, another closely related adenosylcobalamin-dependent rearrangement known to occur in S. cinnamonensis.